BUSINESS PROFICIENCY OF PRIVATE PHYSICIAN PRACTITIONERS IN NYERI COUNTY AND HOW THIS INFLUENCES THE BUSINESS GROWTH OF THEIR PRIVATE PRACTICES - Muyembe, Dr. Victor; Kimani, George; Wanjohi, Gichema (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of this study was to determine the business proficiency of private physician practitioners in Nyeri County and how this influences the business growth of their private practices. Methodology: The study used descriptive research design. Non- probability sampling method was used. In particular, purposive sampling was used. The target population was 31 doctors and the sample size was 31 since a census method was used. The main tool for data collection was questionnaires. Data was analyzed using Pearson correlation analysis. Results: Growth of private physician practice is positively influenced by leadership skills, Accounting and Financial Management skills, Human Resource Management skills and implementation of Information Communication Technology. Unique Contribution to Theory, Practice and Policy: It was recommended that every physician engaged in private medical practice should have at least the basic skills in business management. Private medical practitioners are further encouraged to implement the use of Information Communication Technology in the operation of their practice.